Using Learning Managemant System in Fundamental of Analytical Chemsitry Course: Effect on Students’ Critical Thinking through The Authentic Assessment - Metridewi Primastuti; Erfan Priyambodo; Das Salirawati (TANJAK, 2023)
Critical thinking is the main skill for connecting relationships between chemical science concepts in a coherent environment. Therefore, a learning and evaluation method is needed to help students master the meaning of chemistry to environmental phenomena. The Fundamental of Analytical Chemistry course invites students to study the technique of determining the concentration of a compound. This is relevant to improve their critical thinking skills. This study aims to analyze the effect of the implementation of Technology-based Authentic Assessment (TbAA) on students' critical thinking skills in Fundamental of Analytical Chemistry course. Designed as a pre-experimental, one group pretest-posttest study was applied. A total of 26 undergraduate Chemistry students were included as samples through purposive sampling. TbAA was held for 7 meetings, then critical thinking skills were assessed through essay instruments covering aspects of interpretation, analysis, evaluation, inference. The validity test was carried out theoretically by 2 learning chemists on 4 critical thinking questions that had been developed. After the data was obtained, descriptive statistics and the Wilcoxon test were carried out to answer the research objectives. Based on the results of the analysis, there is a significant difference in students' critical thinking skills after the application of TbAA.